Development of research tools - Gautam, N. C. (Shree, 2005)
Contents of material: Nature and characteristics of research tool. 2/ Principles and steps of research tools. 3/ Item analysis. 4/ Concept of valiability. 5/ Concept of validity. 6/ Qualitative methods in research. 7/ Collaborative education research. 8/ Technologies in educational research. 9/ Internet as a research tool.